Upaya Pendekatan Kedokteran Keluarga pada Seorang Pasien Perempuan 52 Tahun dengan Hiperurisemia di Puskesmas Banda Baro Kabupaten Aceh Utara - Dira Putri Nabila; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
A 52-year-old female patient presented to the non-communicable disease clinic at the Banda Baro Community Health Center with complaints of pain in the right toe joint for the past two weeks. The pain was described as severe, especially when touched or moved. The patient reported that the toe initially became red and swollen, but the redness had subsided by the time she arrived at the clinic. The patient also complained of feeling weak and occasional tingling in the tips of her toes. She admitted to frequently consuming chicken liver and other offal. She mentioned having experienced a similar condition previously, and previous examinations indicated elevated uric acid levels. She had previously taken allopurinol two years ago, obtained from the health center, to alleviate her symptoms. On physical examination, the patient's blood pressure was 120/70 mmHg, heart rate 87 beats per minute, respiratory rate 19 breaths per minute, and temperature 36.5°C. The patient was prescribed allopurinol 2x100 mg. Primary data was obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and completing patient records. Assessment was based on the initial, ongoing, and final holistic diagnosis of the visit. Interventions included education on the importance of clean and healthy living habits, avoiding risk factors, medication adherence, and preventing complications that may arise due to hyperuricemia.